2016
DOI: 10.1007/s10198-016-0774-5
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis and suicides in Spain. Socio-demographic and regional variability

Abstract: These results suggest that the Spanish economic crisis has been associated with suicide rates in 2008, 2009, and 2012. These findings are consistent with the double-dip recession that Spain experienced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…However, the increasing trend found in our analysis may reflect the four years recession that started in 2014, as the increase from 2010 to 2014 was 4.9% in the North and 10.5% in the Northeast, while the increase from 2014 to 2017 was 22% in the North and 17% in the Northeast. The relationship between recession and risk of suicide has been well documented before, from the foreclosure crisis in US 16 to more recent cri-sis in Japan 17 , Spain 18 and in Greece 19 and might happen when socioeconomic programmes are not put in place to mitigate the effect of the crisis.…”
Section: Suicidementioning
confidence: 99%
“…However, the increasing trend found in our analysis may reflect the four years recession that started in 2014, as the increase from 2010 to 2014 was 4.9% in the North and 10.5% in the Northeast, while the increase from 2014 to 2017 was 22% in the North and 17% in the Northeast. The relationship between recession and risk of suicide has been well documented before, from the foreclosure crisis in US 16 to more recent cri-sis in Japan 17 , Spain 18 and in Greece 19 and might happen when socioeconomic programmes are not put in place to mitigate the effect of the crisis.…”
Section: Suicidementioning
confidence: 99%
“…A second area of dispute is related to the possible macroeconomic determinants of increasing suicide rates. In general, unemployment is the most widely used indicator of a financial crisis [ 10 , 11 , 22 ], especially in Mediterranean countries such as Spain [ 23 ]. This measure has been proven to have either inconsistent or contradictory results [ 16 ] since there are two-way relationships that mask these effects, such as the existing between unemployment and mental illness [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed in Spain in the first years of the crisis [18] have reported the same decreasing tendency. However, more recent reports have shown that mortality due to suicide increased after the start of the crisis, especially in men [39,40]. Moreover, two studies based on urban areas did not show an increase in inequalities in suicide mortality during the crisis period [41,42].…”
Section: What Is Already Known and What Does This Study Add?mentioning
confidence: 89%